ТЕОРІЯ АНАЛІЗУ ПОМИЛОК У НАВЧАННІ ІНОЗЕМНОЇ МОВИ (Педагогіка вищої та середньої школи, 2008)
The article investigates some important moments of the theory of error analysis which arose in the 60-70s in the West as an applied research branch of linguistics directed to more successful teaching as well as learning of the foreign language.